A disciplina biologia nas narrativas sobre as mudanças curriculares no Ceará (1992-2016) - Rodrigues, Diego Adaylano Monteiro (2020)
This works aims to understand how the discipline Biology has been structured in the official curricula of Ceará and the curricular experiences in Liceu do Ceará School between 1992 and 2016. The study is connected with the theoretical premises of the critical curricular theories and the history of school’s disciplines and culture. It is based on a qualitative investigation paradigm and is inspired by narrative research. The first research phase focused on the history of this subject through the evaluation of three state curricula plans implemented in 1992, 2000 and 2009. Also, it was based on the voice of its authors and documents about their production contexts such as the state educational legislation, State Education Board’s opinions and resolutions. In the second phase, this investigation focused on the narratives of Liceu do Ceará School’s faculty and alumni, as well as on class diaries of those teachers and other documents in the school’s collection. The analysis comprised the Textual and Discourse Analysis and data was organized in five categories: 1) The production process of the official curricula of Ceará; 2) Principles and guiding concepts of the official curricula; 3) Goals, knowledge and didactic modalities expressed in the curricular plans for the Biology subject; 4) Curricular decisions and the factors that stimulated curricular changes based on the teachers’ careers; 5) The experienced biology curriculum: within the perceived and the experienced curriculum in school. As a result, it was identified that the official biology curricula were built by subgroups formed by technicians from the Ceará State Department of Education, teachers from schools and universities. These productions involved different levels of state teachers participation. In some cases, these teachers had their names omitted and there were also tensions in the implementation. These curricula were influenced by new federal and state legislation, the market logic, pedagogical trends and science teaching movements, which led to aspects of critical curricular thinking and conflicts between academic purposes and social transformation. Regarding The evaluated school, we noticed teacher’s curricular decisions were influenced by their studies background and experience (especially the ones related to school laboratories), distribution of school material (such as books and laboratory materials), the relative appreciation and independency acquired by the teachers. The Official state curricula had a secondary role in the curricular decisions and worked together with the strategies that subtly control teachers. In this sense, narratives revealed teachers’ resistance as shown by the moments when, during classes, they spoke about their fights for better working conditions and about the social realities of the students. In the evaluated historical context, we also realized there was an appreciation for the ecological subjects in the 1990 sand greater appreciation for Genetics and Biotechnology after 2000, as evidenced by the class diaries and official state curricula. Hence, we conclude that the Biology discipline is a social construct based on alliances, tensions and fights in the Ceará curricular history. Also, we showed this discipline was elaborated by different subgroups and that it mixed different curricular pedagogical thoughts and traditions.